2021
DOI: 10.1021/acs.macromol.1c00761
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light Photoinitiation of (Meth)acrylate Polymerization with Autonomous Post-conversion

Abstract: Conversion plateaus rapidly in radical photopolymerizations (RPPs) following discontinuation of irradiation due to rapid termination of reactive radicals, which restricts the wider use of RPPs in applications that involve nonuniform light access including those with attenuated light transmission or irregular surfaces. Based on our recent report of a radical dark-curing photoinitiator (DCPI) that continues polymerization beyond the cessation of irradiation by enabling latent redox initiation with photo-released… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…The incorporation of IBOMA, at a loading of f IBOMA = 0.6 (IE7), did indeed enhance the performance of the adhesive in terms of G 0 when compared at an angular frequency of 5 rad s À1 as it was increased with IBOMA to G 0 = 2.7 Â 10 5 Pa (IE7) compared to G 0 = 4.3 Â 10 3 (PP(EG)T_0.5) for a thiol:ene ratio of 0.5. The corresponding elastic modulus 5 Pa, which suggests a strong adhesive with a high E compared to the values reported for 10 layers of 3 M Scotch tape G 0 = 6.6 Â 10 4 Pa and E ≈ 2:16 Â 10 5 Pa. 51…”
Section: Samplementioning
confidence: 72%
See 2 more Smart Citations
“…The incorporation of IBOMA, at a loading of f IBOMA = 0.6 (IE7), did indeed enhance the performance of the adhesive in terms of G 0 when compared at an angular frequency of 5 rad s À1 as it was increased with IBOMA to G 0 = 2.7 Â 10 5 Pa (IE7) compared to G 0 = 4.3 Â 10 3 (PP(EG)T_0.5) for a thiol:ene ratio of 0.5. The corresponding elastic modulus 5 Pa, which suggests a strong adhesive with a high E compared to the values reported for 10 layers of 3 M Scotch tape G 0 = 6.6 Â 10 4 Pa and E ≈ 2:16 Â 10 5 Pa. 51…”
Section: Samplementioning
confidence: 72%
“…2,4 The low energy requirements, solvent-free formulations, and ambient reaction conditions make photopolymerization one of the most environmentally friendly polymer synthesis methods. 5 Moreover, photopolymerization reactions for synthesizing crosslinked polymer networks are highly efficient as they eliminate auxiliary chemicals, and the suggested synthesis does not produce by-products or waste. The free radical polymerization reaction has an atom economy (AE) factor of 99.8% and a waste factor of 0.001, making it attractive from a green chemistry perspective.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors further reported significant photo-bleaching which reduced the internal filter effect which not only increased the depth of cure prior to the redox component of the mechanistic cascade but also the speed of the light curing to 20% conversion. Importantly, the results showed >35% additional conversion in methacrylate polymers over 25 min (although it is likely to further increase with time) following the initial irradiation to 20% conversion and the ability to rescue under-cured regions post-irradiation [74]. However, whether this can be achieved in all methacrylate based dental polymers is yet to be demonstrated.…”
Section: Dark Curementioning
confidence: 91%
“…However, it has been shown that the depth of cure is product dependent and although adequate polymerisation can be achieved at depth, the bottom is usually less well cured in bulk fill materials compared with conventional materials which is likely due to the lower light irradiances delivered in deeper increments [71]. Although the cure is likely to improve during the post-cure phase [72], conversion plateaus rapidly after the light is switched off as radical production ceases while termination continues [73,74]. Due to this plateau, it has also been reported that the post-cure of some bulk fill materials may exceed the generally accepted 24 h to reach adequate conversion compared with conventional materials [75].…”
Section: Dark Curementioning
confidence: 99%